2022
DOI: 10.31146/1682-8658-ecg-199-3-115-124
|View full text |Cite
|
Sign up to set email alerts
|

Immuno-mediated comorbidity: clinical and pathogenetic aspects of the infl ammatory bowel diseases and spondyloarthritis association

Abstract: Background. The problem of comorbidity is becoming increasingly important in modern medicine and healthcare. A combination of infl ammatory bowel diseases (IBD) and spondyloarthritis (SpA), the genesis of which is closely related to immune infl ammation, can be attributed to the number of comorbid mutually aggravating pathology. In real clinical practice, there is often a late diagnosis of these comorbid processes, which aff ects the quality and eff ectiveness of treatment and worsens the outcomes of diseases.Aim.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…During the experiment, other researchers found that in patients with irritable bowel syndrome, changes in thyroid hormone levels are associated with a moderate increase in proinflammatory cytokines (tumor necrosis factor-alpha, interleukin-1β, interleukin-6 and interleukin-8) and decreased anti-inflammatory cytokine. (interleukin-10) [22].…”
Section: Discussionmentioning
confidence: 99%
“…During the experiment, other researchers found that in patients with irritable bowel syndrome, changes in thyroid hormone levels are associated with a moderate increase in proinflammatory cytokines (tumor necrosis factor-alpha, interleukin-1β, interleukin-6 and interleukin-8) and decreased anti-inflammatory cytokine. (interleukin-10) [22].…”
Section: Discussionmentioning
confidence: 99%